2002
DOI: 10.1177/026461960202000204
|View full text |Cite
|
Sign up to set email alerts
|

The use of the NARA for assessing the reading ability of children with low vision

Abstract: This paper summarises the reading ability data collected from 476 children with low vision using the Neale Analysis of Reading Ability (NARA). The project aimed to generate standard reading ages for pupils with low vision using the NARA reading test. This would enable children's reading to be assessed against their partially sighted peers as well as their fully sighted peers. Standardised reading ages were generated using a linear regression technique to smooth the data. The data shows that the average reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 4 publications
3
21
0
3
Order By: Relevance
“…Relatively little work has been carried out into the reading errors of children with low vision. However, Douglas et al. (2002) tested the reading of 476 children with low vision using an unmodified print version of the NARA.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little work has been carried out into the reading errors of children with low vision. However, Douglas et al. (2002) tested the reading of 476 children with low vision using an unmodified print version of the NARA.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies have shown that children with CVI display orienting responses with longer latencies 19 as well as longer search times. 20 Also, children with other visual impairments (VI o ) due to congenital ocular disorders and/or retinal abnormalities have longer search times 13,14 and lower reading speeds 21,22 compared with children with NV. Furthermore, in adults, visual acuity correlates with performance on visual processing speed tests 23,24 and visual acuity is a significant predictor of reaction times in adults with macular degeneration.…”
mentioning
confidence: 99%
“…As examples of this literature, Douglas et al (2002) and Hill et al (2005) observed delays in speed, accuracy and comprehension of print reading among British children with low vision. They made a distinction between developmental delays in reading and difficulties in access to text, arguing that long-term difficulty in accessing text leads to developmental delays.…”
Section: Access To Print and Delays To Reading Developmentmentioning
confidence: 95%